KONSEP PEMURIDAN DALAM AMANAT AGUNG DAN RELEVANSINYA BAGI GEREJA DAN PENDIDIKAN AGAMA KRISTEN - Darmianus Harefa; Veni Kristin Rompas (Jurnal Ilmiah Wahana Pendidikan, 2023)
The Great Commission delivered by Jesus is a duty and order that must be carried out by everyone who believes in Him. This Great Commission must be applied in daily life. The purpose of writing this article is to see the relevance between Christian Religious Education and the Church in the implementation of the Great Commission. Teaching everyone to make disciples is something that is not easy to carry out, even so this task is a noble task that is mandated for us people who believe in Jesus. The research method in this article is a literature study, in order to obtain various references and information regarding the implementation of the Great Commission in the context of Christian Religious Education and the Church context. The conclusion from this research is that the Great Mandate of Jesus Christ can be carried out and carried out both in schools through teaching Christian Religious Education and can also be carried out in churches as agents in spreading the Gospel of God's Truth, becoming agents who bring about change, impact people in the environment where they live.